Evaluating energy justice metrics in early-stage science and technology research using the JUST-R metrics framework - Arkhurst, Bettina K.; Houghteling, Clara R.; Dutta, Nikita S.; Clarke, Ardelia; Fu, Katherine; Anderson, Kate; Gill, Elizabeth (Frontiers in Environmental Science, 2023)
Embedding principles of energy justice throughout all aspects of clean energy technology research and development (R&D) can facilitate a more just energy transition; yet gaps remain in our understanding of how to best integrate energy justice from the earliest R&D stages. The Justice Underpinning Science and Technology Research (JUST-R) metrics framework has been developed to enable early-stage energy researchers to assess and address justice considerations associated with their research, but the impacts of the framework, and others like it, have yet to be evaluated. This study seeks to evaluate the JUST-R metrics framework in terms of its effectiveness and appeal to early-stage researchers using case studies and qualitative analyses of workshop transcripts. We find that the metrics framework helps researchers identify problems and potential solutions surrounding the energy justice implications of their work and spurs a change in perspective for researchers, but, simultaneously, there is no evidence of solution follow-through within the case study timeframe. Greater institutional support, specialization to research areas, knowledge of energy justice fundamentals, and earlier incorporation of energy justice considerations in research projects arise as factors needed to aid continued use of the framework and pursuit of identified solutions. This evaluation protocol and these findings can serve as a guide for